СПОРТШЫЛАРДЫ ТАЯРЛАЎДАҒЫ КӨП ЖЫЛЛЫҚ ШУҒЫЛЛАНЫЎЛАРДЫҢ ƏҲМИЙЕТИ ҲƏМ ШУҒЫЛЛАНЫЎ ПРИНЦИПЛЕРИ - Мырзамбетов, П.Ш. (FAN va JAMIYAT, 2021)
The article discusses the importance of long-term training in the preparation of athletes and their principles. In other words, the principles of interaction are emphasized, and a broad understanding of the importance of each preparatory process is given and explored.